Improving the Quality of Citizenship Education Learning With the Cooperative Learning Model - Amanda, Dyra (International Journal of Students Education, 2024)
This study aims to analyze the effectiveness of the Cooperative Learning model in enhancing the quality of Civic Education ( PKn ) learning. The study employs a literature review method by analyzing 12 previous studies that examine the impact of Cooperative Learning implementation on aspects such as conceptual understanding, social skills, learning motivation, and students' civic attitudes. The data sources include studies using various approaches, such as experimental, quasi-experimental, classroom action research, and qualitative studies. The findings indicate that Cooperative Learning significantly improves student learning outcomes, both academically and non-academically. Several studies reported an increase in average student test scores by up to 40%, while discussion skills, group collaboration, and understanding of civic concepts also showed substantial improvement. Additionally, this model is proven effective in fostering tolerance, boosting learning motivation, and assisting teachers in addressing the skill gaps among students. In conclusion, Cooperative Learning is an effective teaching method for improving the quality of Civic Education learning. This model not only supports students' academic achievements but also develops essential social skills and civic values. However, challenges such as limited educational facilities in rural areas must be addressed to optimize the implementation of this method.